Formation and development of historical science in the Belarusian State University (1920–50s) - Kakhanouskі, Alіaksandr G.; Yanouski, Aleh A. (Journal of the Belarusian State University. History, 2021)
The article examines the century long way of formation and development of historical science at the Belarusian State University. It is concluded that from the very beginning of the university’s activity, the most important directions of historical research were formed in it. A special place was occupied by Belarusian studies, which became the sphere of professional activity of both historians and archaeologists, ethnographers, source researchers, historiographers, and archivists. At the same time, Russian and Slavic history was also deeply studied and since the 1920s. Belarusian antiquity, media studies, novistics et cetera has originated. It is noted that such a wide range of studies was largely determined by the fact that the university had to train specialists in the relevant fields of knowledge. Historians of BSU initiated the creation of separate research societies and institutions, including the Institute of Belarusian Culture and the Belarusian Academy of Sciences. Highlighted the stages of development of university historical science, which were characterised by their distinctive features and were determined by socio-political factors. The current state of the historical science of BSU is outlined.
Keywords: historical science; historians; Belarusian State University; Belarusian studies; history textbooks; scientific schools; training of scientific personnel